PENGARUH INFLASI, NILAI TUKAR, DAN SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA PERIODE (2010-2024) - Annisa Chania Putri; Habibah Habibah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of inflation, exchange rates, and interest rates on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange during the 2010–2024 period. This study was conducted due to differences in results from previous studies and inconsistencies between empirical conditions and prevailing economic theory. The research method used is a quantitative approach utilizing secondary data. Data collection techniques are carried out through documentation methods. The study population includes all data on inflation, exchange rates, interest rates, and the Jakarta Composite Index during the 2010–2024 period. The research sample uses monthly data from January 2010 to December 2024 which is then processed into an annual average. Data analysis methods used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing using t-tests and F-tests, and coefficient of determination analysis. The results show that inflation partially has no significant effect on the Jakarta Composite Index. The exchange rate partially has a significant effect on the Jakarta Composite Index, while interest rates partially have no significant effect on the Jakarta Composite Index. However, simultaneously, inflation, exchange rates, and interest rates have a significant effect on the Jakarta Composite Index. The findings of this study indicate that the exchange rate has a more dominant influence in influencing the movement of the JCI compared to other macroeconomic variables during the study period.